The Effectiveness of Rubber Bumpers in Reducing the Effects of Earthquake-Induced Pounding between Base-Isolated Buildings - Seyed Mohammad Khatami; Hosein Naderpour; Alireza Mortezaei; Alireza Sharbatdar; Natalia Lasowicz; Robert Jankowski (Applied Sciences, 2022)
The methods for preventing earthquake-induced structural pounding between two adjacent buildings include ensuring a sufficient separation distance between them or decreasing their relative displacement during seismic excitation. Some equations or even specific values of such gap sizes between two buildings have been introduced so as to avoid collisions. Increasing the stiffness of buildings, using tuned mass dampers, applying liquid dampers, or decreasing the mass of the structures may reduce lateral displacements, and therefore pounding can be prevented. On the other hand, the application of base isolation systems may result in the elongation of the natural period of the building, thus increasing the probability of structural pounding. The aim of the present paper is to verify the effectiveness of using rubber bumpers to reduce the negative effects of earthquake-induced pounding between base-isolated buildings. The analysis was conducted for different gap sizes between buildings, as well as for various values of the thickness, number and stiffness of rubber bumpers. The results of the study show that the peak impact force decreases with increasing thickness, stiffness, and number of bumpers. Moreover, the peak impact forces are reduced with increasing gap size. The results of the investigation clearly indicate that the use of additional rubber bumpers can be considered an effective method for reducing the negative effects of earthquake-induced pounding between base-isolated buildings.